Economics: Complex Windows - Salzano, Massimo; Kirman, Alan.; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2005)
This volume contains papers that provide an analysis of topics in the following areas: Agent Based Models, Non-linear Time Series Analysis, Financial Market Dynamics, Econo-physics, Deterministic Chaos, Macroeconomic Dynamics. Economics: Complex Windows, does not present contributions to the sterile debate as to the merits of the different grand, or potentially grand paradigms of economics. Rather it offers a balanced collection of methodological advances which can be applied to concrete economic problems. Starting with a presentation of the "complexity approach" to economics, it goes on to provide a collection of applications to areas such as the analysis of market imperfections, risk assessment, non-linear dynamics, forecasting and highly irregular fluctuations. The tools used help to provide a clearer understanding and a more accurate analysis of these areas of economics. They also highlight the gulf which exists between current economic theory and real economic practice. The basic idea is to encourage economic researchers to embrace a more open and pragmatic approach to economics rather than to reluctantly move in this direction as if it were somehow a betrayal of established dogma. We hope, in this way, to open up avenues which will lead to progress beyond the "holy trinity", (rationality, equilibrium and greed) of modern economics.
Keywords: Finance; Economic theory; Microeconomics; Macroeconomics; Public finance; Economic policy; Economics; Economic Theory/Quantitative Economics/Mathematical Methods; Macroeconomics/Monetary Economics//Financial Economics; Microeconomics; Economic Policy; Finance, general; Public Economics; Electronic books